2021
DOI: 10.1177/00031348211011149
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy and Abdominal Wall Closure Technique Increase the Probability of Postoperative Ventral Incisional Hernia in Patients With Colon Cancer

Abstract: Background Chemotherapy is associated with postoperative ventral incisional hernia (PVIH) after right hemicolectomy (RHC) for colon cancer, and abdominal wall closure technique may affect PVIH. We sought to identify clinical predictors of PVIH. Methods We retrospectively analyzed patients who underwent RHC for colon cancer from 2008-2018 and later developed PVIH. Time to PVIH was analyzed with Kaplan-Meier analysis, clinical predictors were identified with multivariable Cox proportional hazards modeling, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Fifthly, this study data was not collected the details of postoperative adjuvant chemotherapy. The adjuvant chemotherapy for colon cancer was recently associated with a high incidence of IH [ 29 ], however, many prospective randomized studies evaluating the effect of adjuvant chemotherapy were conducted, and none reported an increased risk of IH by any regimen of chemotherapy [ 30 32 ]. So, this study did not analyze the influence of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Fifthly, this study data was not collected the details of postoperative adjuvant chemotherapy. The adjuvant chemotherapy for colon cancer was recently associated with a high incidence of IH [ 29 ], however, many prospective randomized studies evaluating the effect of adjuvant chemotherapy were conducted, and none reported an increased risk of IH by any regimen of chemotherapy [ 30 32 ]. So, this study did not analyze the influence of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, factors such as smoking, traumatic complications[ 30 ], adjuvant chemotherapy for colon cancer[ 31 ], postoperative weight gain[ 32 ], elevated intra-abdominal pressure, and prior abdominal surgeries[ 33 ] are also associated with a higher incidence of IH.…”
Section: Risk Of Ih Following Laparoscopic Colorectal Surgerymentioning
confidence: 99%
“…Studies have demonstrated that the use of monofilament sutures can reduce the incidence of IH[ 47 ]. Partial fascial closure techniques may increase the risk of postoperative abdominal wall hernia[ 31 ]. Hughes abdominal closure experiments have initially shown promise in reducing the risk of IH[ 48 , 49 ], but further clinical validation is still required[ 50 ].…”
Section: Prevention Of Ihmentioning
confidence: 99%